Innovations in water governance: the importance of time. (June 2014) - Eshuis, Jasper; van Buuren, Arwin
Time is often considered to be an inert background against which governance processes evolve. Instead, this article approaches time as a factor that influences the development of innovation processes in water governance. Drawing on two Dutch cases, we analyse perceptions of time and the management of time. Public managers manage time by trying to fix deadlines, by synchronizing different timelines or by imposing their time horizon on the process. Different actors' timeframes may interfere with one another, and this may hinder governance processes. The analysis of time helps to explain the dynamics of governance processes, and this article shows that the alignment of timeframes is a crucial activity in realizing innovations in governance. Points for practitioners: Time is a crucial factor in innovation processes. Actors often have different perceptions of time, including different time horizons and deadlines. Classic time management mainly aims at budgeting time. This article argues for time sensitive governance. An elementary step is to explicate actors' various time-horizons, time cycles and time-budget. Managers need to align short-term time horizons needed in competitive markets, with medium-term views required to carefully develop innovations and embed them in the policy environment. Adaptivity in dealing with time is important to synchronize the development of innovations with developments in the market and governmental organizations.